Criminal Sanctions Against Criminal Acts Of Fund Corruption Social Help - Kristiyadi Kristiyadi; Vincentius Patria Setyawan (CV. Ulil Albab Corp, 2022)
This study aims to analyze the legal arrangements for cases of corruption in social assistance funds and to examine the application of sanctions to perpetrators of corruption in social assistance funds. In this review, this study uses a normative type of research, using a statutory approach that investigates all legal aspects that arise. Primary law sources come from laws and regulations related to cases, while secondary law comes from legal books and journals that are correlated with issues in research. Data collection techniques by reading, recording, quoting, summarizing, and reviewing the information and explanations collected from both the law and the literature. The results of the study reveal that in legal guidelines Number 31 of 1999 amendments to Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption have not explicitly regulated violations of social assistance funds corruption cases, but perpetrators of social assistance corruption violations can be sentenced to death on the grounds that the suspect of social assistance funds corruption made the mistake of taking funds for social assistance for personal or group interests so as to fulfill the elements contained in Article 2 paragraph (2) of Law 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption.This study aims to analyze the legal arrangements for cases of corruption in social assistance funds and to examine the application of sanctions to perpetrators of corruption in social assistance funds. In this review, this study uses a normative type of research, using a statutory approach that investigates all legal aspects that arise. Primary law sources come from laws and regulations related to cases, while secondary law comes from legal books and journals that are correlated with issues in research. Data collection techniques by reading, recording, quoting, summarizing, and reviewing the information and explanations collected from both the law and the literature. The results of the study reveal that in legal guidelines Number 31 of 1999 amendments to Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption have not explicitly regulated violations of social assistance funds corruption cases, but perpetrators of social assistance corruption violations can be sentenced to death on the grounds that the suspect of social assistance funds corruption made the mistake of taking funds for social assistance for personal or group interests so as to fulfill the elements contained in Article 2 paragraph (2) of Law 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption.